General equilibrium theory and international trade - Negishi, Takashi (Amsterdam : North-Holland Pub. Co., 1972)
This book has some chapters devoted to applications in international economics of the ideas developed in other chapters. Although it started with the problem of the optimality and existence of a competitive equilibrium and then devoted a considerable number of pages to the stability problem, both of which are well studied areas of general equilibrium theory, the rest of the book is concerned with such unexplored or unsolved problems as increasing returns, externality, monopolistic competition, second best theory and the dichotomy of price and monetary theories.
"Sole distributors for the U.S.A. and Canada: American Elsevier Publishing Co., inc., New York."
Includes bibliographical references and index.
rpm 26/10/2017
Loans
Keywords: International trade; Economics, Mathematical; Business cycle--Mathematical models